Identifikasi Tingkat Kerawanan Banjir Di Kelurahan Sempaja Timur, Kota Samarinda - Irawan, Shadiq Raditya; Mustofa, Umar; Hidayat, Arief; Kadri, Mohtana Kharisma (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Indonesia, which has a rainy season with an average counted rainfall of 2,898 millimeters per-year, has great potential. Nonetheless, with such potential, the high rainy season can cause various problems, one of which is flooding. East Sempaja Subdisctrict in Samarinda City, become an area that is often hit by floods. This research aims to identify the level of flood disaster vulnerability and formulate flood disaster mitigation strategies in Sempaja Timur Subdistrict to overcome and mitigate the flooding problems that occur. This research uses a non-probability sampling technique with a sample size of 97 households to verify data on the height and duration of floods from BPBD Samarinda City with actual incidents in the field based on point of view of people affected by floods. Based on the results of data collection, it is known that the height of floods that occurs ranges from 10 cm to 150 cm, with a duration of floods ranging from less than 24 hours to more than a week. The analysis method used was overlay analysis, scoring and variable weighting. There are nine variables used, which is land slope, land elevation, rainfall, soil type, distance to river, drainage facilities, floods height, and floods duration. The results of the research show that there are three levels of flood vulnerability, which is, low vulnerability level of 68.92 ha, medium vulnerability level of 403.4 ha, and high vulnerability level of 115.16 ha. Keywords : identification, flood, vulnerability, East Sempaja Subdistrict